Biomimetic Mussel Adhesive Inspired Anchor to Design ZnO@Poly(3‐Hexylthiophene) Hybrid Core@Corona Nanoparticles. Issue 16 (1st June 2015) - Awada, Hussein; Mezzasalma, Leila; Blanc, Sylvie; Flahaut, Delphine; Dagron‐Lartigau, Christine; Lyskawa, Joël; Woisel, Patrice; Bousquet, Antoine; Billon, Laurent
<x xml:space="preserve">Abstract</x> The functionalization of zinc oxide (ZnO) nanoparticles by poly(3‐hexylthiophene) (P3HT) brush is completed by the combination of a mussel inspired biomimetic anchoring group and Huisgen cyclo‐addition "click chemistry." Herein, the direct coupling of an azide modified catechol derivative with an alkyne end‐functionalized P3HT is described. This macromolecular binding agent is used to access core@corona ZnO@P3HT with a stable and homogeneous conjugated organic corona. Preliminary photoluminescence measurement proves an efficient electron transfer from the donor P3HT to the acceptor ZnO nanoparticles upon grafting, thus demonstrating the potential of such a combination in organic electronics.